Spatial Distribution and Health Risk Assessment based on Groundwater Fluoride Enrichment in Gaya, Bihar, India - Ahmad, Shaz; Singh, Reena (Engineering, Technology & Applied Science Research, 2023)
Fluoride can be hazardous to the body if consumed in excess. Fluoride exposure in humans can occur through the consumption of contaminated groundwater. The purpose of this study is to determine the amount of fluoride present in the area under investigation and to determine the health risks associated with its ingestion by adults and children. In accordance with the method recommended by the Environmental Protection Agency, the assessment of the health risk was done using the Chronic Daily Intake (CDI) and Hazard Quotient (HQfluoride). The fluoride in groundwater varies from 0.37 - 2.70mg/L in the study area. According to the sampling results of all locations, the HQfluoride value in adult males ranges from 0.38 to 2.77, 0.34 to 2.45 in adult females, and 0.41–3.0 in children, which is above the permissible limits for most of the sampling locations, indicating significantly higher health risks. The outcomes of this study could be beneficial for organizations in charge of promoting human health.